2020
DOI: 10.1038/s41467-020-18480-y
|View full text |Cite|
|
Sign up to set email alerts
|

A data-driven simulation platform to predict cultivars’ performances under uncertain weather conditions

Abstract: In most crops, genetic and environmental factors interact in complex ways giving rise to substantial genotype-by-environment interactions (G×E). We propose that computer simulations leveraging field trial data, DNA sequences, and historical weather records can be used to tackle the longstanding problem of predicting cultivars’ future performances under largely uncertain weather conditions. We present a computer simulation platform that uses Monte Carlo methods to integrate uncertainty about future weather cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…The use of ACE models including known genetics in analysis of a genetics trial was shown to substantially reduce model residuals and improve heritabilities, potentially improving breeding values, tree selection, and future breeds. The benefits of improved tree breed selection for forest sites are accentuated in the context of climate change ( Dungey et al, 2018 ; D’odorico et al, 2020 ; De Los Campos et al, 2020 ). The ACE method is also advocated for use in general research trial analyses to improve accuracy and precision of results by accounting for environmental variation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ACE models including known genetics in analysis of a genetics trial was shown to substantially reduce model residuals and improve heritabilities, potentially improving breeding values, tree selection, and future breeds. The benefits of improved tree breed selection for forest sites are accentuated in the context of climate change ( Dungey et al, 2018 ; D’odorico et al, 2020 ; De Los Campos et al, 2020 ). The ACE method is also advocated for use in general research trial analyses to improve accuracy and precision of results by accounting for environmental variation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enviromics acts as a central bottleneck for the application of modern genomics-assisted prediction tools, especially for use across multiple environments. Novel approaches have integrated field trial data with DNA sequences using different sources of enviromics, such as linear and nonlinear reaction-norm models (e.g., Jarquín et al, 2014;Morais-Júnior et al, 2018;Millet et al, 2019;Monteverde et al, 2019;Costa-Neto et al, 2020a), crop growth model (CGM) outputs (Heslot et al, 2014;Rincent et al, 2017Rincent et al, , 2019, CGM integrated with GS (Cooper et al, 2016;Messina et al, 2018;Robert et al, 2020) and historical weather records to predict cultivars in years to come (de los Campos et al, 2020).…”
Section: Why Enviromics To Improve Multi-environment Trials For Genomics-assisted Plant Breeding?mentioning
confidence: 99%
“…Progress toward the modernization of the statistical and quantitative genetic models for the analysis of plant breeding in multi-environment trials has become clearer as the availability of genomics, phenomics, and environments information has increased (see, among others, Vargas et al, 1998;Crossa et al, 2010;Burgueño et al, 2012;Heslot et al, 2014;Jarquín et al, 2014;Montesinos-López et al, 2017;Millet et al, 2019;Costa-Neto et al, 2020a;de los Campos et al, 2020;Robert et al, 2020). Thus, we see that all the elements described above offer a clear potential for the acceleration of genetic gains in plant breeding.…”
Section: Interconnection In Modern Plant Breedingmentioning
confidence: 99%
“…This choice is properly arbitrary and depends on the model creator. A grid search including cross-validation was used to determine the values of the ML model hyperparameters [81]. The range of parameter values for the cross-validation procedure was selected based on [75].…”
Section: The Mlp Parameters and Their Valuesmentioning
confidence: 99%